Assessing motility through abdominal sound monitoring - REILLY, RICHARD (IEEE, 1997)
This paper presents the results of an investigation into a computerised system for the assessment of gastrointestinal motility through the recording and analysis of bowel sounds. The system described is aimed primarily at monitoring post-operative recovery. Other potential applications such as a clinical aid in the determination of the effects of drugs on the intestinal tract and as a method of improving the objective diagnosis of motility disorders are also outlined
PUBLISHED
Keywords: Administrative Staff Authors